Establishment Exits in Germany: The Role of Size and Age - Daniel Fackler; Claus Schnabel; Joachim Wagner (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2012)
Using comprehensive data for West Germany, this paper investigates the determinants of establishment exit. We find that between 1975 and 2006 the average exit rate has risen considerably. In order to test various "liabilities" of establishment survival identified in the literature, we analyze the impact of establishment size and put a special focus on differences between young and mature establishments. Our empirical analysis shows that the mortality risk falls with establishment size, which confirms the liability of smallness. The probability of exit is substantially higher for young establishments which are not more than five years old, thus confirming the liability of newness. There also exists a liability of aging since exit rates first decline over time, reaching a minimum at ages 15 to 18, and then rise again somewhat. The determinants of exit differ substantially between young and mature establishments, suggesting that young establishments are more vulnerable in a number of ways.
Keywords: L20; L26; C10; 330